THE ECONOMIC IMPACT OF COVID-19 - Hudd, Emily; Coulibaly, Louphou (Minneapolis, Minnesota : Abdo Publishing, 2021)
In late 2019, health officials noticed a new disease spreading in Wuhan, China. They named it COVID-19. Within a few months, it became a pandemic that dramatically changed life for nearly everyone on Earth. Millions of people became sick, and hundreds of thousands died. Leaders ordered whole states and countries to stay home to slow the disease's spread. Companies closed or went out of business. Meanwhile, health-care workers on the front lines saved lives and raced to find treatments. In the Core Library Guide to COVID-19, readers will learn about the disease, how it spread across the globe, and the ways it has changed society. Many of the world's largest economies shut down almost overnight as nations tried to slow the spread of COVID-19. These measures saved lives, but they also cost millions of jobs and shuttered many companies - some temporarily, others forever.
Includes bibliographical references and index.
Keywords: COVID-19 (Disease) -- Juvenile literature; Coronavirus infections -- Juvenile literature; Communicable diseases -- Prevention -- Juvenile literature; Epidemics -- Economic aspects -- Juvenile literature